Rancang Bangun Sistem Penyortir Warna Berbasis Mikrokontroler Atmega328p Pada UD Ilham Jaya Makmur - Anus wuryanto - Universitas BSI Jakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
A color sorter system using TCS3200 sensor is based on Atmega328p Microcontroller with C language programming. Color sensor is for differentiating color data which is taken. The system consists of hardware and software. The hardware consists of ATmega328p microcontroller, TCS3200 color sensor. The microcontroller software in this study is made using the Arduino IDE application 1.6.8. For activating, the sensor needs to take the data of each color object which is brought closer. Data retrieval using servo motor that serves to replace the sensor position. The position of the object retrieval must be precise, in this case is intended the color sensor can read the color of the exact object. If there is an inappropriate position after the data retrieval and testing process, then the resulting output can’t be able detect the color. The color object will perform according to the exact position when capturing the color data. Microcontroller to process the input data that have been taken. After the process is complete then the color sensor testing result can be seen from the LCD as t he color information which is displayed, during the data retrieval of the color object then the object is forwarded by the servo motor towards the container glass. So the objects can be grouped according to their color.Keywords: Color sorter, TSC3200 color sensor. Sistem penyortir warna menggunakan sensor TCS3200 berbasis mikrokontroler Atmega328p dengan pemrograman bahasa C. Sensor warna untuk membedakan warna data yang diambil. Sistem terdiri atas perangkat keras dan perangkat lunak. Perangkat keras terdiri atas mikrokontroler ATmega328p, sensor warna TCS3200, Perangkat lunak mikrokontroler dalam penelitian ini dibuat dengan menggunakan aplikasi IDE Arduino 1.6.8. Untuk mengaktifkan sensor perlu pengambilan data setiap objek warna yang didekatkan. Pengambilan data menggunakan motor servo yang berfungsi untuk menggantikan sensor posisi. Posisi pengambilan objek harus tepat, hal ini bertujuan supaya sensor warna bisa membaca warna objek yang tepat. Jika terjadi posisi yang tidak tepat setelah proses pengambilan data dan pengujian, maka output yang dihasilkan tidak bisa mendeteksi warna tersebut. Objek warna akan tampil sesuai dengan posisi yang tepat saat pengambilan data warna. Mikrokontroler untuk memproses input yang telah diambil. Setelah proses selesai maka hasil pengujian sensor warna bisa dilihat dari LCD sebagai informasi warna yang ditampilkan saat pengambilan data objek warna kemudian objek diteruskan oleh motor servo kearah gelas penampung, sehingga objek dapat dikelompokkan sesuai warnanya.Kata Kunci : Penyortir warna, Sensor warna TSC3200.